Linking College Learners’ Competence in Information and Communication Technology and Learning Styles during the COVID-19 Pandemic (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of the study was to determine the learning styles and Information and Communication Technology Competence of university students in the course of the COVID19 pandemic. It also aims to identify possible associations related to ICT Competence and the students’ learning styles. A descriptive and correlational quantitative approach was applied in the study and used a non-probabilistic sample of 686 students in a state university in the Philippines. The results showed that the students’ dominant learning style is collaborative and seconded by dependent. This means that university students in the course of the COVID19 pandemic exposed to flexible learning modalities learn best when given opportunities to exchange ideas to small group discussions than large group lectures. However, a significant number of students lack intellectual interest and learn only what is asked of them. Meanwhile, students' ICT skills and attitudes are closely connected to their learning styles. Collaborative learners have a higher level of ICT competence than the other groups. Furthermore, the findings revealed that students' learning styles are strongly linked to their college programs. Other variables, such as ICT-related burnout levels, should be examined to see whether they have a possible mediation impact on ICT competence.